2018
DOI: 10.1002/ecs2.2401
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil fungal communities and vegetation following afforestation with Pinus tabulaeformis on the Loess Plateau

Abstract: Soil fungi have important effects on plant performance and nutrient cycling. To understand the dynamics of the soil fungal community and their response to changes in understory plants and soil properties after afforestation, we investigated a cropland site (CL) and three Pinus tabulaeformis plantation sites with different ages (15, 30, and 45 yr) in the Ziwuling Mountains, Loess Plateau, China. Afforestation increased the soil organic carbon (SOC), total nitrogen (TN), total phosphorus (TP), NO À 3 -N, and NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 86 publications
(98 reference statements)
0
19
0
Order By: Relevance
“…In study plots, the soil pH ranged from 4.2 to 4.3, indicating an acidic nature of the soil; this is somewhat lower than the ideal soil pH range for regular growth, which is 4.5 to 6.5 and metabolism of the Chinese fir plant [20,26]. Previous research depicted that soil pH is an important factor in determining the composition of fungal communities [27,28]. This is an important factor because soil pH can affect fungal diversity and population dynamics by affecting nutrient availability or imposing physiological constraints on fungal growth.…”
Section: Discussionmentioning
confidence: 83%
“…In study plots, the soil pH ranged from 4.2 to 4.3, indicating an acidic nature of the soil; this is somewhat lower than the ideal soil pH range for regular growth, which is 4.5 to 6.5 and metabolism of the Chinese fir plant [20,26]. Previous research depicted that soil pH is an important factor in determining the composition of fungal communities [27,28]. This is an important factor because soil pH can affect fungal diversity and population dynamics by affecting nutrient availability or imposing physiological constraints on fungal growth.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, redundancy analysis (RDA) also exhibited that soil pH, NH 4 + -N, AP, and AK significantly affected the fungal community structures ( Figure 5 a, Table 3 ), and it has been well established that soil pH is the most significant determinant for shaping fungal communities [ 73 , 74 , 75 ]. The SEM also explained that changes in fungal communities were mainly affected by the soil pH ( Figure 5 b), and soil pH has been identified as a crucial factor in determining the structure of the soil fungal population [ 59 , 68 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…We can infer that soil physicochemical properties changing with biochar concentration could contribute to the distinct variations in fungal community structures. Previous studies also showed that soil pH is the most important variable for shaping the fungal communities [ 64 , 65 ]. This is because soil pH may affect the fungal diversity and community composition by modifying nutrients availability or putting physiological limits on fungal growth.…”
Section: Discussionmentioning
confidence: 99%